PENGARUH SOCIAL MEDIA MARKETING DAN e-WOM TERHADAP BRAND IMAGE SERTA DAMPAKNYA TERHADAP MINAT BELI - Yani, Sulisti; Wijayanto, Gatot; Musfar, Tengku Firli (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of social media marketing, electronic word of mouth and brand image as a mediation on interest in buying. The population in this study includes generation Z or teenagers at the age of 11-26 years in Pekanbaru City. The sampling technique used was Non-Probability Sampling, which does not provide the same requirements for each person. The number of samples used in this study using the Hair formula with a total of 145 respondents. To test the hypothesis in this study, path analysis was used with the help of SPSS version 26 software. Based on the results of the testing, it can be concluded that social media marketing, electronic word of mouth and brand image have a significant positive effect on buying interest. Social media marketing and electronic word of mouth have a significant positive effect on buying interest through brand image as a mediating variable. Suggestions for further writers, recommendations for further research are that this research can be further developed by adding other variables such as celebrity endorsers, influencer marketing, social media advertising, online advertising, online promotions or other variables that are in accordance with this research.